MAKNA TANDA RAFA’ ALIF DAN HIKMAHNYA DALAM KEHIDUPAN UNTUK MENCAPAI KESUKSESAN - Putra, Mulya; Aqila Az Zahra, Nayyara (Jurnal Al-Hibru, 2025)
This research focuses on one aspect of i'rab, namely the sign rafa' alif, which is not only grammatically meaningful but also holds deep symbolic and spiritual value. This study aims to uncover the meaning and wisdom behind the rafa' alif sign as reflected in the structure of the Arabic language and its application in life, especially as an inspiration to achieve true success. Using the descriptive content analysis method combined with Focus Group Discussion (FGD), this study analyzes the use of the letter "أن" and its role in forming the mashdar mu'awwal in Surah Al-A'raf. The results show that the sign of i'rab rafa' alif is not only a grammatical marker in ism mutsanna, but can also be interpreted as a symbol of spiritual improvement, recognition of effort, and encouragement towards a more meaningful life. Rafa' alif reflects the degree raised because of sincerity, patience, and consistency in righteous deeds. In addition, rafa' alif is also a representation of life values such as integrity, sincerity, and the importance of process in achieving life goals. In the context of learning Arabic, the understanding of i'rab and its signs, including alif as a sign of rafa', makes an important contribution not only to mastering the structure of the language, but also to the formation of noble character.